Developing Opportunity-Identification Capabilities in the Classroom: Visual Evidence for Changing Mental Frames - Muñoz-Canales, C (2011)
We consider how the development of students capabilities for identifying business opportunities is underpinned by a change in their opportunity- identification mental frames. We observe that students find it difficult to verbally articulate how their performance has changed, and yet such changes are reflected through radical shifts in their visual representations of entrepreneurship. We conclude that entrepreneurship courses need to change the way students perceive reality and interpret information to enable them to more effectively identify new business opportunities.